Relationship between exercise pressure gradient and haemodynamic progression of aortic stenosis - Ringle, Anne; Levy, Franck; Ennezat, Pierre-Vladimir; Le Goffic, Caroline; Castel, Anne-Laure; Delelis, François; Menet, Aymeric; Malaquin, Dorothée; Graux, Pierre; Vincentelli, André; Tribouilloy, Christophe; Maréchaux, Sylvestre (Archives of cardiovascular diseases, 2017)
We hypothesized that large exercise-induced increases in aortic mean pressure gradient can predict haemodynamic progression during follow-up in asymptomatic patients with aortic stenosis. We retrospectively identified patients with asymptomatic moderate or severe aortic stenosis (aortic valve area<1.5cm2 or<1cm2) and normal ejection fraction, who underwent an exercise stress echocardiography at baseline with a normal exercise test and a resting echocardiography during follow-up. The relationship between exercise-induced increase in aortic mean pressure gradient and annualised changes in resting mean pressure gradient during follow-up was investigated. Fifty-five patients (mean age 66±15 years; 45% severe aortic stenosis) were included. Aortic mean pressure gradient significantly increased from rest to peak exercise (P<0.001). During a median follow-up of 1.6 [1.1–3.2] years, resting mean pressure gradient increased from 35±13mmHg to 48±16mmHg, P<0.0001. Median annualised change in resting mean pressure gradient during follow-up was 5 [2–11] mmHg. Exercise-induced increase in aortic mean pressure gradient did correlate with annualised changes in mean pressure gradient during follow-up (r=0.35, P=0.01). Hemodynamic progression of aortic stenosis was faster in patients with large exercise-induced increase in aortic mean pressure gradient (≥20mmHg) as compared to those with exercise-induced increase in aortic mean pressure gradient<20mmHg (median annualised increase in mean pressure gradient 19 [6–28] vs. 4 [2–10] mmHg/y respectively, P=0.002). Similar results were found in the subgroup of 30 patients with moderate aortic stenosis. Large exercise-induced increases in aortic mean pressure gradient correlate with haemodynamic progression of stenosis during follow-up in patients with asymptomatic aortic stenosis. Further studies are needed to fully establish the role of ESE in the decision-making process in comparison to other prognostic markers in asymptomatic patients with aortic stenosis. L’objectif principal de l’étude était de déterminer si une élévation importante du gradient moyen trans-aortique à l’échocardiographie d’effort permet de prédire une progression hémodynamique rapide au cours du suivi chez les patients porteurs d’un rétrécissement aortique asymptomatique. Nous avons identifié rétrospectivement les patients asymptomatiques porteurs d’un rétrécissement aortique modéré ou sévère (surface fonctionnelle aortique<1,5cm2 ou<1cm2) sans dysfonction ventriculaire gauche, ayant bénéficié d’une échographie d’effort initiale avec test d’effort normal puis d’une échographie de repos au cours du suivi. La relation entre l’élévation du gradient moyen à l’effort et la progression du gradient moyen de repos au cours du suivi a été étudiée. Cinquante-cinq patients ont été inclus (âge moyen 66±15 ans), 45 % (n=25) étaient porteurs d’un rétrécissement aortique sévère. Une augmentation significative du gradient moyen était retrouvée entre le repos et le pic de l’effort (p<0,001). Après un suivi médian de 1,6 [1,1–3,2] ans, le gradient moyen de repos augmentait de 35±13mmHg à 48±16mmHg (p<0,0001) avec une augmentation médiane de 5 [1,8–11,1] mmHg/an. L’élévation du gradient moyen à l’effort était corrélée à la progression annuelle du gradient moyen au cours du suivi (r=0,35, p=0,01). La progression de la sténose aortique était plus rapide chez les patients ayant une élévation importante du gradient moyen à l’effort (≥20mmHg) en comparaison aux patients ayant une faible élévation du gradient moyen à l’effort (<20mmHg), avec une progression annuelle médiane du gradient moyen de 19 [6–28] vs. 4 [2–10] mmHg/an respectivement (p=0,002). Des résultats similaires étaient retrouvés dans le sous-groupe des 30 patients présentant un rétrécissement aortique modéré. Cette étude établit un lien entre l’élévation importante du gradient moyen à l’effort et la progression hémodynamique rapide de la sténose au cours du suivi, chez les patients porteurs d’un rétrécissement aortique asymptomatique. D’autres études seront nécessaires pour établir de façon définitive la place de l’échocardiographie d’effort en comparaison avec les autres marqueurs pronostiques chez les patients porteurs d’un rétrécissement aortique asymptomatique.